Evaluation of altered brain activity in type 2 diabetes using various indices of brain function: A resting-state functional magnetic resonance imaging study - Zhang, Ge; Liu, Taiyuan; Wei, Wei; Zhang, Rui; Wang, Huilin; Wang, Meiyun (Frontiers in Human Neuroscience, 2023)
Background Type 2 diabetes mellitus (T2DM) has been demonstrated an increased risk factor of cognition decline. Previous researches reported that T2DM patients were associated with alterations of brain function based on resting-state functional imaging (rs-fMRI) analyses. In this study, we combined multiple rs-fMRI indices to investigate the abnormal functional changes among T2DM patients and to gain fresh insight of underlying mechanisms of cognition impairment induced by T2DM. Methods 52 T2DM patients and age-, sex- matched control participants were included in this study. Amplitude of low frequecny fluctuations, regional homogeneity and voxel-mirrored homotopic connectivity values were calculated to represent the status of spontaneous neural activity. Cognitive evaluation was performed for all participants. Besides correlations between rs-fMRI indices and clinical parameters, relationships between different rs-fMRI indices were also determined in T2DM patients. Results Compared with control subjects, the indices of intrinsic brain function showed significantly concordant alterations in several brain areas including bilateral cerebellum posterior lobe, left inferior temporal gyrus, parahippocampal gyrus and supplementary motor area. Although no abnormal brain region was detected by all three indices at the same time, the indices presented significant correlation in most regions revealed by each single method. In the T2DM patients, the fasting glucose was correlated with decreased neural activity in the surrounding areas of left insula and inferior frontal gyrus. While the MoCA results did not differ between two groups, the cognition performance was negatively correlated with mean values of ReHo extracted from left occipital lobe and superior cerebellum cortex, and the mean values of VMHC extracted from left caudate and precentral gyrus. Conclusion The current study demonstrated a more enriched picture showing the brain functional alterations reflected by the combination of ALFF, ReHo and VMHC measurements in T2DM patients. The widespread abnormalities mainly involved in motor and sensory processing function may provide another insight in examining the neurological pathophysiology of T2DM-related neurodegeneration.